A combined posterior reversed L-shaped and anterolateral approach for two column tibial plateau fractures in Caucasians: A technical note. Issue 12 (December 2015) - Hoekstra, H.; Rosseels, W.; Luo, C.-F.; Nijs, S.
Abstract: Objective: Open reduction and internal fixation of two column posterior and lateral tibial plateau fractures through a combined posterior reversed L-shaped and anterolateral approach in floating position in Caucasians. Indications: Two column posterior and lateral tibial plateau fractures. Contraindications: Tibial plateau fractures that do not involve the posterior and lateral column. Surgical technique: The patient is positioned in floating position, a reversed L-shaped skin incision is made, the posterior column after lateral retraction of the medial head of the gastrocnemius muscle is exposed, and the posterior fragments are reduced and fixed. Subsequently, flexion and varus stress on the knee is applied, an anterolateral skin incision is made, the lateral column is exposed, and the lateral fragments are reduced and fixed. Conclusion: Despite a different physique as Asians, a combined posterior reversed L-shaped and anterolateral approach in a floating position for the surgical treatment of two column posterior and lateral tibial plateau fractures is technically possible in Caucasians. In our experience, this combined approach is an excellent strategy in most patients for surgical treatment of two column posterior and lateral column fractures.